Sudden cardiac death in young athletes, a literature review and special considerations in Asia - Halabchi, F.; Seif-Barghi, T.; Mazaheri, R. (Asian Journal of Sports Medicine, 2011)
Sudden cardiac death (SCD) in a young athlete is rare, but catastrophic. Exercise acts as a risk factor for SCD in people with cardiovascular disease. A diversity of cardiovascular disorders including hypertrophic cardiomyopathy, congenital coronary anomalies, arrhythmogenic right ventricular dysplasia, dilated cardiomyopathy, aortic rupture due to Marfan syndrome, myocarditis, valvular disease and electrical disorders (Wolff-Parkinson-White syndrome, long QT syndrome, Brugada syndrome), as well as commotio cordis represent the common causes of SCD in young athletes. As the outcome of lethal cardiovascular disorders is not reversible except in few cases, effective measures should be addressed to reduce the burden of sudden cardiac death in young athletes. Currently, two types of recommendations are proposed by American and European countries. It seems that there are some special considerations in Asia, entirely different from North America or Europe, which warrant more comprehensive research on epidemiology and etiology of SCD in young Asian athletes by country and evaluation of current national preventive strategies and their achievements in decreasing the risk. Using these data and considering regional restrictions, an expert group will be able to plan a practical and feasible preventive strategy.